The Alliance to “Civilize” the East Indies Government and Catholic Missionaries in Manggarai-Flores - Ricardo Vargas Posada; Bernard Adeney-Risakotta; Dicky Sofjan (Jurnal Kawistara, 2020)
The present paper deals with the reestablishment of Catholic missionary activity in the Dutch East Indies during the nineteenth century and the first decades of the twentieth. It pays particular attention to the arrival of missionaries in western Flores in the twentieth century, when conversion to Catholicism saw a spectacular growth in the Manggarai region. It delves into the complex interaction of government officials, missionaries and local leaders and how particular social practices and economic modes of production were advanced. It aims to understand how the particular set of civilizing discourses that the missionaries upheld at the time dovetailed with the objectives of the Dutch colonial government. It relies on Critical Discourse Analysis to analyze the contents of the article The Scientific Role of the Missionary, by Monseigneur Alexander Le Roy, superior general of the Congregation of the Holy Spirit, which appeared in prominent publications of the main Catholic congregation working in Flores during the twentieth century, the Society of the Divine Word (SVD). However, it demonstrates that the ideologues of Catholic missiology of the time, such as Monseigneur Le Roy, went beyond the civilizing discourses on development. Furthermore, it argues that many of the progressive stances that characterize the church in Flores today can be traced back to the ideas espoused by their missionary forefathers.